Method for repairing lithium iron phosphate
Through the process of burning, sand grinding, spray granules, and high -temperature sintering, the problem of incomplete reaction of lithium -ion battery orthopedic material recycling in the recycling of the orthopedic battery orthopedic material recycling and insufficient hybrid reactions of the lithium supplement agent can be achieved. Restore the maximum and environmental friendly sustainable development.
Patent Information
- Application Number
- CN202411470995.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-01-24
AI Technical Summary
In the prior art, when recovering the positive electrode material of lithium-ion batteries, there is a problem that the residual organic matter removal of the electrode sheet is insufficiently removed and the lithium supplement agent is insufficiently mixed, resulting in poor performance of the repair material.
By burning, mixing mixed, sand grinding, spraying, drying lithium and high -temperature sintering, it forms a secondary structure with better stability and improves the performance of lithium iron phosphate material.
Effectively improved the performance of lithium iron phosphate materials, improved the utilization rate of valuable metals, reduced the environmental pollution caused by waste batteries, and helped promote the sustainable development of the new energy industry.
Smart Images

Figure BDA0005094684590000071 
Figure BDA0005094684590000072
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of recycling of waste lithium-ion batteries and recycling of electrode materials, and in particular to a method for repairing lithium iron phosphate. Background Art
[0002] Lithium iron phosphate (LFP) is a lithium-ion battery cathode material with a relatively mature process after years of development. It has become the cathode material with the largest output and usage. The lithium-ion battery prepared by it has a high gram capacity, good cycle stability and high temperature resistance safety characteristics, and is widely used in medical equipment, electronic equipment, mining machinery, aerospace, ocean exploration, new energy vehicles and other technical fields. Since China began to develop and manufacture lithium iron phosphate cathode materials on a large scale, especially with the development and commercialization of new energy vehicles, the production capacity and application scope of lithium iron phosphate have exceeded other cathode materials such as lithium cobalt oxide, nickel cobalt manganese ternary, and lithium manganese oxide, becoming one of the most important lithium-ion cathode materials. In this process, a large number of waste lithium-ion batteries and unqualified lithium iron phosphate cathode materials are generated every year. In addition, because the demand for lithium resources has gradually increased in the past two years, the raw materials for manufacturing lithium battery cathode materials such as lithium carbonate and lithium hydroxide have risen sharply in price. How to efficiently recycle lithium battery cathode materials has become one of the hot issues in the lithium battery industry research, and will also become one of the important core competitiveness of lithium battery companies in the future.
[0003] A Chinese patent application (publication number: CN113764765A) provides a method for recycling positive electrode active materials in batteries. The method is to soak the positive electrode plate powder recovered from the lithium-ion battery in an NMP solution, dry the material after removing the PVDF binder, add the dried powder material to the eutectic lithium salt of LiNO3 and LiOH, and sinter at high temperature to obtain a repair product; the advantage of this method is that the entire recycling process is relatively simple and the process feasibility is strong; the disadvantage is that the degree of removal of the organic matter remaining in some plates is not thorough, resulting in the performance of the repair material being much different than before.
[0004] The Chinese patent application (publication number: CN113991101A) proposes directly mixing the lithium iron phosphate material to be repaired, the conductive agent, the lithium replenisher and the binder to make a repaired battery electrode. The advantage is that the operation is simple, but the disadvantage is that the lithium replenisher and the lithium iron phosphate material to be repaired are not fully mixed and reacted, resulting in a poor repair effect.
[0005] In order to improve the utilization rate of valuable metals, reduce the environmental pollution caused by the scrapping of waste batteries, and help promote the sustainable development of the new energy industry, the present invention studies and designs a method for repairing lithium iron phosphate. Summary of the invention
[0006] Therefore, the technical problem to be solved by the present invention is to overcome the above-mentioned defects, thereby providing a method for repairing lithium iron phosphate.
[0007] In order to solve the above problems, the present invention provides a method for repairing lithium iron phosphate, which comprises the following steps:
[0008] S1: calcining and removing impurities from the recovered lithium iron phosphate powder;
[0009] S2: mixing the calcined lithium iron phosphate powder with a mixture containing an iron source, a carbon source and an additive to obtain a mixture I;
[0010] S3: granulating the mixture I to obtain granulated particles;
[0011] S4: mixing the granulated particles with a mixture containing a lithium source, and drying to obtain a repair precursor;
[0012] S5: performing high temperature sintering on the repair precursor to complete the repair of lithium iron phosphate.
[0013] Further, in step S1, the calcination conditions are:
[0014] The sintering environment requires an oxygen content of ≤30PPM, a calcination temperature of 200°C-650°C, and a calcination time of 2-10h.
[0015] Furthermore, in step S2, the molar ratio of the calcined lithium iron phosphate powder to the iron source, the carbon source and the additive is 1:0.05-0.20:0.02-0.1:0.001-0.05, based on the molar number of lithium element, iron element and carbon element.
[0016] Furthermore, the iron source is selected from one or more soluble or insoluble iron compounds such as ferric orthophosphate, ferrous oxalate, ferric oxide, ferric acetate, etc.;
[0017] The carbon source is selected from one or more of sucrose, citric acid and glucose;
[0018] The additive is selected from at least one of azo compounds and alkane compounds.
[0019] Furthermore, the azo compound is selected from at least one of methyl orange, Congo red and Sudan red;
[0020] The alkane compound is selected from at least one of n-butane, n-hexane, n-heptane and cyclohexane.
[0021] Furthermore, the mixture containing the iron source, the carbon source and the additive and the mixture containing the lithium source both further include a solvent;
[0022] The solvent is selected from at least one of water, ethanol and isopropanol;
[0023] The amount of the solvent used is 5-10 times the amount of the mixture containing the iron source, the carbon source and the additive and the mixture containing the lithium source.
[0024] Furthermore, the mixing method in step S2 is sand grinding;
[0025] The sand grinding conditions are:
[0026] The particle size D50 during sand milling is 100nm-500nm, and the sand milling time is 1-5 hours.
[0027] Furthermore, in step S3, the granulation is performed by spray granulation;
[0028] The spray granulation conditions are:
[0029] The small particles are made into agglomerated spherical secondary particles by spraying;
[0030] The granulated particles have a porous secondary particle structure with relatively uniform size.
[0031] Further, in step S4, the molar ratio of the granulated particles to the lithium source is 1:0.02-0.1, based on the molar number of lithium element;
[0032] The lithium source is selected from one or more of lithium carbonate, lithium hydroxide, lithium acetate and lithium phosphate;
[0033] The drying conditions are:
[0034] The equipment used in the drying process is a belt dryer, the drying temperature range is 80℃-200℃, and the moisture content of the material after drying is ≤10PPM.
[0035] Furthermore, the high temperature sintering conditions are:
[0036] The high temperature sintering temperature is 600°C-900°C, and the high temperature sintering time is 5-20h.
[0037] The lithium iron phosphate repair method provided by the present invention has the following beneficial effects:
[0038] 1. The present invention improves the performance of the material by subjecting the recycled lithium iron phosphate material to calcination, impurity removal, re-granulation, high-temperature sintering and other processes. Compared with other recycling process methods, this method forms a secondary structure with better stability through additives and special processes, so that the material performance is restored to the greatest extent; it improves the utilization rate of valuable metals, reduces environmental pollution caused by the scrapping of waste batteries, and helps promote the sustainable development of the new energy industry;
[0039] 2. The present invention also involves that the recycled materials are not limited to a single pure lithium iron phosphate substance, and the lithium iron phosphate materials recovered after disassembling the battery can also be recycled and repaired;
[0040] 3. The present invention also adds special additives and surfactants through the spraying process involved, so that the prepared secondary particles have a special structure, that is, there are micro holes on the surface of the spherical secondary particles, which improves the efficiency of lithium replenishment and the performance of the finished lithium iron phosphate. DETAILED DESCRIPTION
[0041] The present application discloses a method for repairing lithium iron phosphate, comprising the following steps:
[0042] S1: calcining and removing impurities from the recovered lithium iron phosphate powder;
[0043] S2: mixing the calcined lithium iron phosphate powder with a mixture containing an iron source, a carbon source and an additive to obtain a mixture I;
[0044] S3: granulating the mixture I to obtain granulated particles;
[0045] S4: mixing the granulated particles with a mixture containing a lithium source, and drying to obtain a repair precursor;
[0046] S5: performing high temperature sintering on the repair precursor to complete the repair of lithium iron phosphate.
[0047] The method of the present application improves the performance of the material by calcining and removing impurities, re-granulating, and high-temperature sintering the recovered lithium iron phosphate material. Compared with other recycling process methods, this method forms a secondary structure with better stability through additives and special processes, so that the material performance can be restored to the greatest extent.
[0048] The recycled materials involved in the method of the present application are not limited to a single pure lithium iron phosphate substance, and the lithium iron phosphate materials recovered after disassembling the battery can also be recycled and repaired.
[0049] The spraying process involved in the method of the present application adds special additives and surfactants, so that the prepared secondary particles have a special structure, thereby improving the efficiency of lithium replenishment and the performance of the finished lithium iron phosphate.
[0050] The manufacturing equipment of the method of the application is simple and the process is easy to engineer.
[0051] The recovery of lithium iron phosphate material in the method of the present application is achieved by the following steps: disassembling the waste lithium iron phosphate battery after discharge to separate the positive electrode sheet, and then crushing and separating the positive electrode sheet to obtain the positive electrode material and aluminum foil, which are further subjected to gravity screening and impurity removal to obtain the waste lithium iron phosphate material for the next step of repair.
[0052] The present application also discloses some embodiments, in which in step S1, the calcination conditions are:
[0053] The sintering environment requires an oxygen content of ≤30PPM, a calcination temperature of 200°C-650°C, and a calcination time of 2-10h.
[0054] The present application also discloses some embodiments. In step S2, the molar ratio of the calcined lithium iron phosphate powder to the iron source, the carbon source and the additive is 1:0.05-0.20:0.02-0.1:0.001-0.05, calculated by the molar number of the element, the iron element and the carbon element.
[0055] The present application also discloses some embodiments, wherein the iron source is selected from one or more soluble or insoluble iron compounds such as ferric orthophosphate, ferrous oxalate, ferric oxide, ferric acetate, etc.;
[0056] The carbon source is selected from one or more of sucrose, citric acid and glucose;
[0057] The additive is selected from at least one of azo compounds and alkane compounds.
[0058] The present application also discloses some embodiments, wherein the azo compound is selected from at least one of methyl orange, Congo red and Sudan red;
[0059] The alkane compound is selected from at least one of n-butane, n-hexane, n-heptane and cyclohexane.
[0060] The present application also discloses some embodiments, wherein the mixture containing an iron source, a carbon source and an additive and the mixture containing a lithium source both further include a solvent;
[0061] The solvent is selected from at least one of water, ethanol and isopropanol;
[0062] The amount of the solvent used is 5-10 times the amount of the mixture containing the iron source, the carbon source and the additive and the mixture containing the lithium source.
[0063] The present application also discloses some embodiments, wherein the mixing method in step S2 is sand grinding;
[0064] The sand grinding conditions are:
[0065] The particle size D50 during sand milling is 100nm-500nm, and the sand milling time is 1-5 hours.
[0066] The present application also discloses some embodiments, wherein the granulation in step S3 is performed by spray granulation;
[0067] The spray granulation conditions are:
[0068] The small particles are made into agglomerated spherical secondary particles by spraying;
[0069] The small particles are made into agglomerated spherical secondary particles by a spray drying granulator of model PGL-B.
[0070] The granulated particles have a porous secondary particle structure with relatively uniform size.
[0071] The present application also discloses some embodiments, in step S4, the molar ratio of the granulated particles to the lithium source is 1:0.02-0.1, calculated on the basis of the moles of lithium element;
[0072] The lithium source is selected from one or more of lithium carbonate, lithium hydroxide, lithium acetate and lithium phosphate;
[0073] The drying conditions are:
[0074] The equipment used in the drying process is a belt dryer, the drying temperature range is 80℃-200℃, and the moisture content of the material after drying is ≤10PPM.
[0075] The present application also discloses some embodiments, wherein the high temperature sintering conditions are:
[0076] The high temperature sintering temperature is 600°C-900°C, and the high temperature sintering time is 5-20h.
[0077] The specific method is as follows:
[0078] Vacuum furnace calcination: Place the recovered lithium iron phosphate powder material in a vacuum sintering furnace to ensure that the oxygen content is less than or equal to 30PPM. The sintering temperature range is 200℃-650℃, the sintering time is 2-10 hours, and the material is collected after sintering is completed.
[0079] Sand grinding and mixing: Add iron source, carbon source, additives and water to the vacuum calcined recycled materials according to the repair materials, and mix them evenly through sand grinding. The sand grinding time is 1-5 hours, and the particle size D50 during sand grinding is 100nm-500nm. After sand grinding, the material to be sprayed is obtained.
[0080] Spray drying: The sand-ground material to be sprayed is prepared into porous secondary particles of relatively uniform size through a spray drying system.
[0081] Drying lithium supplementation: The sprayed granular material, lithium source and water are fully mixed and stirred, and dried through a belt dryer to obtain a dry material to be burned. The molar ratio of the granulated particles to the lithium source is 1:0.02-0.1 based on the molar number of lithium element. The drying temperature ranges from 80℃ to 200℃. The moisture content of the material after drying is ≤10PPM.
[0082] High temperature sintering: The material to be sintered is sintered at a high temperature of 600°C-900°C, with nitrogen protection (oxygen content ≤30PPM), and a sintering time of 5 hours-20 hours to obtain a repaired lithium iron phosphate material.
[0083] Comparative Example 1
[0084] The recovered lithium iron phosphate powder material was collected after high-temperature sintering at 500°C for 2 hours and recorded as sample 1.
[0085] Comparative Example 2
[0086] The recovered lithium iron phosphate powder material was collected after high-temperature sintering at 500°C for 2 hours. The molar ratio of the material to be repaired: iron source: carbon source: lithium source: surfactant was 1:0.2:0.003:0.05:0.002, wherein the iron source was ferric orthophosphate, the carbon source was glucose, the surfactant was n-butane, and the lithium source was lithium carbonate. The material to be repaired, the iron source, the carbon source, the surfactant and water were mixed to obtain a spray material, which was granulated again, added with a lithium source and a certain amount of water, and then dried to obtain a material to be fired. The material to be fired was sintered at 750°C for 10 hours to obtain a repaired lithium iron phosphate material, recorded as sample 2.
[0087] Comparative Example 3
[0088] The recovered lithium iron phosphate powder material was collected after high-temperature sintering at 500°C for 2 hours. The molar ratio of the material to be repaired: iron source: carbon source: lithium source: surfactant was 1:0.2:0.003:0.2:0.002, wherein the iron source was ferrous oxalate, the carbon source was glucose, the surfactant was n-butane, and the lithium source was lithium phosphate. The material to be repaired, the iron source, the carbon source, the surfactant and a certain amount of water were mixed to obtain a spray material, which was granulated again, added with a lithium source and a certain amount of water, and then dried to obtain a material to be fired. The material to be fired was sintered at 750°C for 10 hours to obtain a repaired lithium iron phosphate material, recorded as sample 3.
[0089] Comparative Example 4
[0090] The recovered lithium iron phosphate powder material was collected after high-temperature sintering at 500°C for 2 hours. The molar ratio of the material to be repaired: iron source: carbon source: lithium source: surfactant was 1:0.1:0.004:0.1:0.002, wherein the iron source was ferric oxide, the carbon source was glucose, the surfactant was an azo compound, and the lithium source was lithium acetate. The material to be repaired, the iron source, the carbon source, the surfactant and a certain amount of water were mixed to obtain a spray material, which was granulated again, added with a lithium source and a certain amount of water, and then dried to obtain a material to be fired. The material to be fired was sintered at 750°C for 10 hours to obtain a repaired lithium iron phosphate material, recorded as sample 4.
[0091] The obtained samples 1-4 were subjected to performance tests.
[0092] 1. Test its performance, pH value and specific surface area data.
[0093] 2. The unrepaired iron phosphate material was directly made into battery pole pieces for electrical performance testing. The ratio of the battery pole pieces was active material: conductive agent: binder = 90:5:5. The active material was lithium iron phosphate, the conductive agent was Super P conductive agent, the binder was PVDF, the electrolyte concentration of the electrolyte was 1.2 mol / L, and the solvent ratio was EC: DMC: EMC = 1:1:1. Button cells were made and the first charge and discharge efficiency and rate performance were tested. The data are shown in Tables 1 and 2.
[0094] Table 1
[0095]
[0096] Table 2
[0097]
[0098] It can be seen from Table 1 and Table 2 that the repair method proposed in the present invention effectively improves the comprehensive performance of lithium iron phosphate. The repair effects of Examples 2 and 4 are better. Example 3 has some negative impact on the performance due to the change in the ratio of elements. Better results can be achieved by combining other compounds and optimizing the formula.
[0099] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principle of the present invention shall be included in the protection scope of the present invention. The above description is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and variations can be made without departing from the technical principles of the present invention. These improvements and variations should also be regarded as the protection scope of the present invention.
Claims
1. A method for repairing lithium iron phosphate, characterized in that: The following steps are involved: S1: calcining and removing impurities from the recovered lithium iron phosphate powder; S2: mixing the calcined lithium iron phosphate powder with a mixture containing an iron source, a carbon source and an additive to obtain a mixture I; S3: granulating the mixture I to obtain granulated particles; S4: mixing the granulated particles with a mixture containing a lithium source, and drying to obtain a repair precursor; S5: performing high temperature sintering on the repair precursor to complete the repair of lithium iron phosphate.
2. The method for repairing lithium iron phosphate according to claim 1, characterized in that: In step S1, the calcination conditions are: The sintering environment requires an oxygen content of ≤30PPM, a calcination temperature of 200°C-650°C, and a calcination time of 2-10h.
3. The method for repairing lithium iron phosphate according to claim 1, characterized in that: In step S2, the molar ratio of the calcined lithium iron phosphate powder to the iron source, the carbon source and the additive is 1:0.05-0.20:0.02-0.1:0.001-0.05, based on the molar number of lithium element, iron element and carbon element.
4. The method for repairing lithium iron phosphate according to claim 1, characterized in that: The iron source is selected from one or more soluble or insoluble iron compounds such as ferric orthophosphate, ferrous oxalate, ferric oxide, ferric acetate, etc.; The carbon source is selected from one or more of sucrose, citric acid and glucose; The additive is selected from at least one of azo compounds and alkane compounds.
5. The method for repairing lithium iron phosphate according to claim 4, characterized in that: The azo compound is selected from at least one of methyl orange, Congo red and Sudan red; The alkane compound is selected from at least one of n-butane, n-hexane, n-heptane and cyclohexane.
6. The method for repairing lithium iron phosphate according to claim 1, characterized in that: The mixture containing the iron source, the carbon source and the additive and the mixture containing the lithium source both further include a solvent; The solvent is selected from at least one of water, ethanol and isopropanol; The amount of the solvent used is 5-10 times the amount of the mixture containing the iron source, the carbon source and the additive and the mixture containing the lithium source.
7. The method for repairing lithium iron phosphate according to claim 1, characterized in that: The mixing method in step S2 is sand grinding; The sand grinding conditions are: The particle size D50 during sand milling is 100nm-500nm, and the sand milling time is 1-5 hours.
8. The method for repairing lithium iron phosphate according to claim 1, characterized in that: In step S3, granulation is performed by spray granulation; The spray granulation conditions are: The small particles are made into agglomerated spherical secondary particles by spraying; The granulated particles have a porous secondary particle structure with relatively uniform size.
9. The method for repairing lithium iron phosphate according to claim 1, characterized in that: In step S4, the molar ratio of the granulated particles to the lithium source is 1:0.02-0.1, based on the molar number of lithium element; The lithium source is selected from one or more of lithium carbonate, lithium hydroxide, lithium acetate and lithium phosphate; The drying conditions are: The equipment used in the drying process is a belt dryer, the drying temperature range is 80℃-200℃, and the moisture content of the material after drying is ≤10PPM.
10. The method for repairing lithium iron phosphate according to claim 1, characterized in that: The high temperature sintering conditions are: The high temperature sintering temperature is 600°C-900°C, and the high temperature sintering time is 5-20h.
Citation Information
Patent Citations
Recycling method and recycling equipment for positive electrode active material of lithium ion battery
CN113764765A
Lithium supplementing method for lithium iron phosphate lithium ion battery and lithium iron phosphate lithium ion battery
CN113991101A